Altered Glucagon Response to Oral Glucose in Individuals at Different Stages of Type 1 Diabetes Development - Kontola, Helena; Crisóstomo, Luís; Löyttyniemi, Eliisa; Koskenniemi, Jaakko J.; Veijola, Riitta; Toppari, Jorma; Kero, Jukka (Oxford University Press, 2026)
Context
Autoimmune destruction of beta cells and their functional decline precedes the clinical onset of type 1 diabetes. However, altered alpha-cell function and hyperglucagonemia may contribute to the development of hyperglycemia and ketoacidosis at onset.
Objective
In this cross-sectional study, we analyzed glucagon concentrations during an oral glucose tolerance test (OGTT) in individuals at early stages of type 1 diabetes to understand the role of alpha-cell function in the disease process.
Methods
We recruited 47 participants, aged 4–25 years, from the Finnish Diabetes Prediction and Prevention (DIPP) study, categorized them into the following groups: islet autoantibody (IAb) negative, single IAb positive, and stages 1-3 of type 1 diabetes. Glucagon levels were measured during a six-point OGTT using a conventional radioimmunoassay, alongside insulin, C-peptide, glucose and glucagon-like peptide-1 (GLP-1).
Results
Fasting plasma glucagon levels increased with disease progression. The longitudinal patterns of glucagon concentrations during the OGTT differed significantly between groups, with a paradoxical 15-minute glucagon increase observed only in individuals at early stage 3 of type 1 diabetes.
Conclusion
These findings highlight the need for prospective studies to further elucidate the role of alpha-cells in disease progression and support testing pharmacotherapies aimed at improving both alpha- and beta-cell functions during disease development.